Cochlear Dysfunction after Kanamycin Injection in Multidrug Resistant Tuberculosis Patients - Brahmono, Aditya; Purnami, Nyilo; Surarso, Bakti (Folia Medica Indonesiana, 2020)
Background: Longterm exposure to aminoglycoside such as kanamycin to cochlear cells is known to be associated with damage to outer hair cells in the organ Cortiand type 1 sensory hair cells in the vestibular organs which ultimately causes permanent damage to hair cells. Hair cell damage occurs from the basal cochlea (high frequency area) to the apex cochlea (low frequency area) and followed by damage from the auditory nerve. Evaluation of cochlear dysfunction on multidrug resistant tuberculosis (MDR TB) patients have been rarelyreported in the literature based on distortion product otoacoustic emission (DPOAE).Objectives: To prove cochlear dysfunction after kanamycin injection in MDR TB patient based on DPOAE examination of the overall frequencies and specific frequency. Methods: An observational longitudinal analytic with pre and post design without control group conducted in the infection division of MDR TB Outpatients Pulmonology Department and Otorhinolaryngology Community division of ORL-HNS Department Dr. Soetomo general hospital Surabaya, within 3 months in 2018, 15 ear with the best baseline examination were taken by consecutive sampling and statistical analysis for cochlear dysfunction based on overall frequency and specific frequency DPOAE examination using Mc Nemar test. Results: Based on DPOAE examination of overall frequencies there was no cochlear dysfunction (p > 0.05) but a significant difference was found at frequency of 10,000 Hertz (Hz) (p = 0.002 ). Conclusion:On ototoxicity monitoring there was no cochlear dysfunction after 4 weeks Kanamycin injection but cochlear dysfunction occurs at a specific frequency of 10,000 Hz.